From Hyperconsumption to Conscious Choice – Changes in Market Trends - Urszula Anisiewicz (Journal of Modern Science)
Objectives The aim of this article is to analyze contemporary trends in consumer behavior as a foundation for building competitive advantage. The text discusses changes occurring in the consumption sector, modern consumer trends in the markets, their determinants, and characteristic features and manifestations. The first part will be a characterization of the current consumer, followed by an overview of global trends among buyers. The next section will present the profile of the Polish consumer, including their expectations and needs.